The Press and the Internet: Competition or Complementary? - Kotowska, Agata (Culture & Society, 2010)
The author’s considerations concern the relationship in the period of fundamental changes in technology and culture between the press and the Internet — two media which are different in both form and function. The influence of the press is changing which is shown in the diminishing sales worldwide, and the significance of the Internet is increasing. The systematic contraction of the market for the press is caused by several factors. The competitiveness of the Internet increases with the increasing participation of the young generation in social life. At the same time there is a deep cultural transformation underway which involves the increasing domination of the pictorial environment, the marginalization of the word, the shallowness which replaces previous values. There are many possible futures for the press. The most probable is that it will adapt in form and will continue to exist in the media market. The influence of the press on future societies remains unclear.